PERAN GROWTH MINDSET DALAM PENDIDIKAN ABAD 21: SEBUAH TINJAUAN LITERATUR - Koto, Rahmat Desman; Giatman, M.; Ernawati, Ernawati; Wagino, Wagino; Sulastri, Ayu (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: 21st-century education faces increasingly complex and dynamic challenges, demanding skills beyond academic knowledge. The growth mindset, a concept introduced by Carol Dweck, describes the belief that a person's intelligence and abilities can develop through effort, the right strategies, and environmental support. This article presents a literature review on the role of a growth mindset in 21st-century education. The review results show that the growth mindset plays an important role in increasing student motivation and resilience and supporting active engagement and better academic achievement. In addition, the implementation of the growth mindset also has a positive impact on teacher competency development and entrepreneurship education. This article explores the benefits, challenges, and strategies for implementing a growth mindset to understand its role in creating an adaptive and inclusive learning environment. A more effective and transformative approach to education can be created by better understanding the growth mindset.Keywords: Growth Mindset, 21st Century Education, Student Motivation, Inclusive Learning, Teacher Development.